PENENTUAN KORELASI TINGKAT KEMATANGAN BUAH ALPUKAT (Persea americana mill) TERHADAP GRAVITASI SPESIFIK - Jusuf Wahyudi; Roni Herdian Saputra (UNIVED Press, Universitas Dehasen Bengkulu, 2016)
Social community need to food in general and horticulture in particular from year to year continues to increase along with the growth of population too. This will result an increased need for nutrition and consumption patterns including avocado fruit contains many nutrients needed by human. In this study, 36 ( Thirty six ) Pleces of avocado which each take the data GSp is left at room temperature and then contolled every day to find pleces that correspond to each code. After a long day and that all avocado fruit over ripe the find corelation value ( r ) between GSP value ( Variable Xi ) with ripening time ( Variable Yi ). From this study obtainable correlation value between GSp value avocado fruit (Variable Xi) with ripening time ( Variable Yi ), r = 0,71. From this value r get t aritmetic = 5,336. In the real level a = 0,05 and dk = 30-2 = 3428 get ttable = 2, 048 it turs out t aritmetic > t table 5,336,1 > 2,048 so that Ha accepted and Ho benied or correlation between specific gravity value with increase avocado fruit maturity significant. Key words : Avocado Fruit, Specific Gravity, correlation, Maturity Level.